A diagnosis of the plasma waves responsible for the explosive energy release of substorm onset. Issue 1 (December 2018) - Kalmoni, N.; Rae, I.; Watt, C.; Murphy, K.; Samara, M.; Michell, R.; Grubbs, G.; Forsyth, C.
Abstract During geomagnetic substorms, stored magnetic and plasma thermal energies are explosively converted into plasma kinetic energy. This rapid reconfiguration of Earth's nightside magnetosphere is manifest in the ionosphere as an auroral display that fills the sky. Progress in understanding of how substorms are initiated is hindered by a lack of quantitative analysis of the single consistent feature of onset; the rapid brightening and structuring of the most equatorward arc in the ionosphere. Here, we exploit state-of-the-art auroral measurements to construct an observational dispersion relation of waves during substorm onset. Further, we use kinetic theory of high-beta plasma to demonstrate that the shear Alfven wave dispersion relation bears remarkable similarity to the auroral dispersion relation. In contrast to prevailing theories of substorm initiation, we demonstrate that auroral beads seen during the majority of substorm onsets are likely the signature of kinetic Alfven waves driven unstable in the high-beta magnetotail. The origin of geomagnetic substorms is still uncertain due to lack of comprehensive quantitative analyses. Here, the authors construct an observational dispersion relation of auroral forms that correspond to the explosive energy release from substorm onset.